Análise das proteínas relacionadas a formação de metástase em linhagens de adenocarcinoma gástrico - VALENTE, Tárik Olívar de Nunes (Universidade Federal do Pará, 2014)
Gastric cancer is a serious public health problem worldwide. The high incidence of advanced tumors with poor survival by metastasis, especially in the north, made us realize the comparative study of strains of metastatic gastric adenocarcinoma (AGP01) with gastric adenocarcinoma without metastasis (ACP02) by proteomic evaluation of cell motility that may be related to the formation of these metastasis. Proteomic study was conducted strains AGP01 and ACP02 through the technique of high performance liquid chromatography 2D Nanoultra (UPLC) together with nanoESI - (MSE mudpit) and functional analysis of differentially expressed proteins in the Ingenuity Pathways Analysis (IPA) software. We observed 19 proteins with increased expression in AGP01 lineage regarding ACP02, which are related to movement, organization and cell morphology, where we suggest that ACTB, ANXA1, LGALS1, IQGAP1, EZR, MSN, MYH9 and S100A11 proteins, according to our findings and supported by the research literature is associated with metastasis of gastric adenocarcinomas. Other proteins showed strong expression in our study, but its expression in the research literature is related to the dissemination routes only other tumors, such as breast (RAB5C), lung (PLS1 and CAP1), rectum (ACTN1) and GIST (SYNE2). Conflicting with our study, the expressions of CAPZA1, FLNA and FLNC protein, were observed in the literature as an inhibitor of tumor advancement, where the expression of MYL6, MYL6B and ACTN2 proteins first appear as being related to cell motility, invasion and metastasis in cancer.